An Eye for an Ear: Fifth Business and La grosse femme d'a côté est enceinte - Reid, Gregory J. (Studies in Canadian Literature, 1989)
This article is, in part, a response to Philip Stratford's All the Polarities, a book which discusses the differences between French and English novels. Robertson Davies's Fifth Business and Michel Tremblay's La grosse femme -- both of which are peculiarly absent from the study -- juxtapose the material world with that of the mythic or magic. Davies's novel contains an exteriorizing, distancing, literate style, while the style of Tremblay's novel is immediate, sensuous, and oral. The two novels are similar in terms of characterization, theme, and symbolism; as well, they share a kind of mystical fatalism that tends to undermine political ideology.